Efektivitas Bimbingan Belajar Orang Tua Di Rumah Selama Masa Pademi Di Desa Ibul Kecamatan Simpang Teritip Kabupaten Bangka Barat - Mili, Mili; Amrina, Mira; Nurjanah, Muliani Siti; Lita, Nia Nurul; Mulia, Vima (IJoCE: Indonesian Journal of Counseling and Education, 2021)
Learning guidance carried out by parent for children is very important in the family generally the child is an interaction relationship, everything that is strengthened by the child affects the family and on the other hand, the family provides the basis for shaping moral behavior and education in children. The porpose education is to contain a description of values that are noble, appropriate, correct and beautiful for education. One aspect of improving human resources is continuously improved and renovated from all aspects. Education is a human effort to expand the horizons of knowledge in order to to shape value and attitude.